FACTORS INFLUENCING INVESTMENT DECISIONS IN PROPERTY AND REAL ESTATE SUB-SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Safrizal, Safrizal; Istiqomah, Nur; Masril, Masril (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2024)
The purpose of this study is to ascertain how liquidity, profitability, and investment opportunities affect stock investment decisions in companies in the Property and Real Estate subsector listed on the Indonesia Stock Exchange between 2018 and 2021. During the conduction of this study companies in the Property and Real Estate subsector are made up of 65 companies. Purposive sampling was used to select a sample of 17 companies. Quantitative data were used in this research. Secondary data from the company's financial reports serve as the data source. The examination results show that liquidity somewhat affects corporate share choices, productivity and venture open doors to some extent meaningfully affect corporate security choices. In the meantime, it demonstrates that stock investment decisions are influenced positively by liquidity, profitability, and investment opportunities.